The Influence of Monitoring and Evaluation Reports On Sustainability of Donor-Funded Community-Based Education Projects: A Case of Arumeru District, Arusha Tanzania - Daniel John, Wilson; Pallangyo, Samson Emanuel (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study was to assess the influence of monitoring and evaluation Reports on sustainability of donor-funded community -based education projects in Arumeru district. The purposive sampling technique was used to select the participants. the study used a total of 102 participants. The study used a qualitative approach whereby interview and focus group discussion method were used during collection of data. An interview was used to gather data from the project implementers, whereas data from community members was collected through focus group discussion.  Data were analyzed using Content Analysis method.The findings revealed that, , sustainability of donor-funded community-based education projects in Arumeru District lay down on community participation and project implementers. Sustainability of donor-funded community-based education projects require effective monitoring, and evaluation, as well as resource mobilization. The findings recommended that, community participation should be improved through provision of education, and effective communication to the people or community members. Provision of education and effective communication will rise up awareness for the community members about their participation roles in the sustainability of donor-funded community-based education projects in Tanzania. Also, project implementers should focus on building the capacity of the local community to make sure the project’s sustainability. This includes training community members in project management, leadership, and technical skills. By empowering the community, they will better be equipped with skills and knowledge that will help them to maintain and run the project after the donor funding had ended. Measurement and evaluation reports hold stakeholders accountable for the resources they have committed to the project. By providing regular updates on the project’s progress. Also, measurement and evaluation reports ensure that stakeholders remain engaged and motivated to continue their support.